The Influence of Digital Marketing and Brand Image to Build Interest in Visiting Tourists in the Recovery of the Tourism Sector - Lilis Jayanti; Annisa Maharani Bella Pratiwi; Dita Aulia Rahma; Fernanda Kayisa Putri; Intan Shafa Sulistyo Aji; Purwita (Politeknik Negeri Bandung, 2023)
The tourism sector is currently facing a post-COVID-19 recovery process. Marketing played an important role in the recovery of this tourism sector. Both tourist attractions and the government have started to move again to find the right strategy in marketing. This study aims to analyze the role of digital marketing and brand image in the interest of visiting tourists as part of the recovery of the tourism sector. Data were collected at The Lodge Maribaya as a research locus by interviewing 123 tourists who visited tourist attractions through a questionnaire instrument. By using scoring and path analysis, it is found that Digital Marketing significantly influences Brand Image. Apart from that, digital marketing and brand image also significantly affect tourist interest in visiting. This shows that digital marketing and brand image can be an effective marketing strategy in the context of recovering the tourism sector.